(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Although 3D printing has become of increasing interest in the medical field and the demand for biodegradable polymers has rapidly developed, there are only a few additively manufactured, biodegradable implants on the market. Due to the thermosensitive behavior of such polymers, processing and sterilization of biodegradable implants and the side effects on their degradation have still not been sufficiently studied. The effects of fused filament fabrication (FFF) as well as low-temperature sterilization (H2O2 plasma and gamma radiation) on poly(p-dioxanone) (PPDO) and its degradation behavior were assessed. To quantify PPDO in vitro degradation the differently sterilized samples and a non-sterilized control group were immersed in phosphate buffered solution (PBS) over 4 weeks. Surface morphology, thermal and mechanical properties and molecular weight change were investigated directly after processing and at regular time intervals of immersion. Within this work, printability of thermosensitive PPDO via FFF was successfully demonstrated. Thermal characteristics, molecular weight (Mw) and inherent viscosity (IV) were not significantly affected by the printing process. Further, the investigation of the different sterilization methods presented that H2O2 plasma did not significantly harm the thermosensitive polymer whereas gamma radiation lowered Mw and IV statistically significant (p < 0.001). After being immersed in PBS, non-sterilized samples did not show any change of surface morphology, plasma-sterilized samples revealed small microcracks after two weeks while gamma-sterilized samples had already shown small microcracks directly after being radiated which further deteriorated over immersion duration. Mw and yield strength decreased for all samples. However, gamma-sterilized samples were affected the most. In addition, cell proliferation tests proved the cytocompatibility of degraded PPDO independently of the sterilization method. To conclude, we demonstrated that FFF and H2O2 plasma sterilization are well suited for processing thermosensitive, biodegradable PPDO. This research is meant to support the establishment of adequate production and sterilization methods for biodegradable implants.